Resistant Starch Content and Glycaemic Index of Sago (Metroxylon spp.) Starch and Red Bean (Phaseolus vulgaris) Based Analogue Ric - Wahjuningsih, Sri Budi; Marsono, Y.; Praseptiangga, Danar; Haryanto, Bambang (Pakistan Journal of Nutrition, 2016)
Foods with low glycaemic index (GI) are part of the functional aliments recommended for patients with diabetes mellitus. These foods can be produced from materials with high amylose and/or high dietary fibre content by using specific processing technologies that increase their resistant starch content. Here, analogue rice formulations were prepared using sago and red beans as main materials, employing extrusion technology. We determined their resistant starch (RS) content and GI to evaluate their potential as functional foods for diabetics. Six formulations were tested: pure sago analogue rice (BS100) and five sago analogue rices with the addition of 5, 10, 15, 20 and 25% red bean flour (BSKM5, 10, 15, 20 and 25, respectively). The GIs were determined for 20 healthy volunteers. RS contents of BS100, BSKM5, 10, 15, 20 and 25 analogue rices were 12.25, 11.80, 11.18, 10.97, 10.24 and 9.28%, respectively. The lowest GI value was obtained with BS100 (40.7), while BSKM5 and BSKM10 had GIs of 48.3 and 50.4, respectively. Analogue rice BSKM15 and 20 had medium GIs, 68.8 and 69.5, respectively and BSKM25 was included in the high GI category (76.5). Pure sago analogue rice (BS100) and analogue sago rice with red bean flour added up to 10% (BSKM5 and 10) were included within low GI category, making them potential functional foods for type 2 diabetics.